На темной стороне Луны - Вайнер Георгий Александрович (АСТ, 2002)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 39599 / Цена: 49.50 / Сис.шифр: Р2 / Авт.знак: В 14 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6